Darma dan Kesetaraan: Kiprah Perempuan di Pura Amrta Jati - Putri Chaerun Nisa; Siti Nadroh (Inklusiva: Jurnal Studi Agama-Agama, 2025)
This research examines how religious people and the Hindu community view the changing roles of women in social and religious contexts at Pura Amrta Jati Cinere. This study also investigates new ways of understanding Hindu scriptures that support gender equality and examines how Hindu religious leaders responded to these changes. The research results show that doctrinally, Hinduism actually supports gender equality through the concepts of Ardhanariswara and Shakti, but patriarchal norms in society still pose an obstacle to its implementation. Currently, Hindu women at Pura Amrta Jati are increasingly valued as ritual leaders and important participants in social life, which has a positive impact on the community in terms of spiritual, social, and cultural aspects. There are still some existing social challenges that need to be reflected upon and become the focus of education to promote progress in gender equality within the practice of Hinduism.